KARAKTERISTIK KIMIA YOGHURT SINBIOTIK DENGAN PENAMBAHAN TEPUNG HANJELI (Coix lacryma-jobi L.): CHEMICAL CHARACTERISTICS OF SYNBIOTIC YOGURT WITH THE ADDITION OF HANJELI FLOUR (Coix lacryma-jobi L.) - Dewiarum Sari; Sari Wiji Utami (Universitas Boyolali, 2026)
Synbiotic yogurt is yogurt made by combining probiotics and prebiotics that can increase functional value because they have a positive impact on health. Commercial starter